2014
DOI: 10.1111/jrh.12082
|View full text |Cite
|
Sign up to set email alerts
|

Unclaimed Health Care Benefits: A Mixed‐Method Analysis of Rural Veterans

Abstract: Results suggest that lack of awareness of VHA health care benefits may be the biggest barrier identified by rural veterans. Targeted outreach and education efforts related to eligibility for rural veterans are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Our findings imply that interventions that reduce travel such as telemedicine should be targeted at older patients, particularly those in rural areas, while interventions that make transportation more accessible and reliable may be most effective among urban residents. However, pinpointing the diverse and particular barriers encountered during treatment will most likely require the use of qualitative research methods, potentially in the form of interviews or focus groups, among rural and urban patients with cancer (33,34). Recognizing the importance of urban/rural differences in the context of significant variation in treatment timing may help policymakers, clinicians, and other stakeholders to better identify and treat women at risk for suboptimal care and reduce observed outcome disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings imply that interventions that reduce travel such as telemedicine should be targeted at older patients, particularly those in rural areas, while interventions that make transportation more accessible and reliable may be most effective among urban residents. However, pinpointing the diverse and particular barriers encountered during treatment will most likely require the use of qualitative research methods, potentially in the form of interviews or focus groups, among rural and urban patients with cancer (33,34). Recognizing the importance of urban/rural differences in the context of significant variation in treatment timing may help policymakers, clinicians, and other stakeholders to better identify and treat women at risk for suboptimal care and reduce observed outcome disparities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 38% of veterans responding to the 2014 National Survey of Veterans agreed with the following statement: “Veterans who can afford to use other sources of health care should leave VHA [Veteran's Health Administration] to those who really need it.” This may reflect the general lack of knowledge regarding VA resource allocation, and of the VA's ability to bill private health insurers. A small qualitative study of nonenrolled rural veterans confirmed most were unaware that private health insurance carriers reimbursed VA for care provided to insured veterans for nonservice‐connected conditions …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some veterans may be reluctant to report private insurance to the VA due to a misperception that having private insurance disqualifies veterans from being eligible for VA health care enrollment . Official VA websites postguidance on this topic, stating “Your insurance coverage or lack of insurance coverage does not determine your eligibility for treatment at a VA health care facility,” but some privately insured veterans may still refrain from disclosing their private health insurance to the VA for fear it will disqualify them from obtaining benefits, or that it might lead to higher premiums for individual plans.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that the most common reason that potentially eligible rural Veterans did not use VA care was that they were unaware of their eligibility (Wittrock et al, 2015). Among rural non-enrolled Veterans, it was a common perception that VA enrollees were poor and were required to have experienced combat and a subsequent injury or disability (Wittrock et al, 2015). These findings are cause for concern because rural Veterans tend to have more physical health comorbidities and likely a greater need for VA health care services than other Veterans (Weeks et al, 2004).…”
Section: Enabling Characteristicsmentioning
confidence: 99%
“…Veterans may not fully understand their eligibility for VA health care benefits, services available at VA, how to apply for services, and the need for treatment for their condition (U.S. Government Accountability Office, 2011; Weeks et al, 2004;Wittrock, Ono, Stewart, Reisinger, & Charlton, 2015). One study found that the most common reason that potentially eligible rural Veterans did not use VA care was that they were unaware of their eligibility (Wittrock et al, 2015). Among rural non-enrolled Veterans, it was a common perception that VA enrollees were poor and were required to have experienced combat and a subsequent injury or disability (Wittrock et al, 2015).…”
Section: Enabling Characteristicsmentioning
confidence: 99%